Practice related factors that may impact on postpartum care for mothers and infants in Australian general practice: a cross-sectional survey. Issue 1 (December 2016) - Brodribb, Wendy; Mitchell, Benjamin; van Driel, Mieke
Abstract Background While there is a significant focus on the health and well-being of women during pregnancy, labour and birth, much less emphasis is placed on the care of postpartum women and their infants in primary care following the birth. Some studies have investigated the role of GPs in postpartum care, and others examined facilitators and barriers to mothers accessing care. However there is little information available to investigate the effect of practice related factors on access to care of mothers and infants at this time. Methods A 20-item questionnaire for completion by the practice managers was mailed to 497 general practices in Southern Queensland, Australia between February and July 2013. Questionnaire items included practice demographics, practice procedures and personnel including appointment scheduling, billing, practice nurse function and qualifications and a free-text option for comments. Descriptive statistics are presented as numbers and percentages. Chi Squared test compared practice location with methods of identification of postpartum women, practice size with other Queensland data and ANOVA compared practice size with the number of postpartum appointments. Logistic regression was used to predict variables that were related to booked appointment times. Free text responses were grouped in common themes. Results The response rate was 27.4 %. At 67.2 % of the practices, mothers had to self-identify as needing a postpartum consultation and most consultations were allocated 15 minutes or less. Only 20 % of practices accepted the government insurance payment (bulk-billing) for all maternal and infant services, with more practices bulk-billing children only. Out-of-pocket expenses ranged from 10-60. Nearly 80 % of practice nurses saw postpartum mothers or infants 'nearly always' or 'sometimes'. Approximately 30 % had midwifery or child health training. There were higher odds of longer booked appointment times for solo practitioner practices (unadj OR 3.30 95%CI 1.03-10.57), but no other variables predicted booked appointment times Conclusions This study identified a number of practice related factors that, if addressed, could positively impact on postpartum care. These include ensuring ongoing practice relationships to assist with booking appropriate consultation times and guaranteeing that there are no financial impediments to women accessing care. Some factors can easily be adapted within practices. Others would require changes of policy at a local or national level.